Economic sustainability enhancement by the integration of renewable energy in a deregulated system: A study - V. Ravindranadh Chowdary; Sadhan Gope; Subhojit Dawn; Md. Minarul Islam; Taha Selim Ustun (Energy Exploration & Exploitation)
The global energy system is continuously changing, driven by increasing power demands and the urgent need to address environmental challenges. This highlights the necessity of integrating renewable energy sources with existing thermal power plants into deregulated power systems. This paper explores how the incorporation of renewable energy can enhance economic sustainability, focusing on the vital roles of smart grids (SGs) and microgrids. By leveraging these advanced grid technologies, more effective integration of renewable energy can be achieved, leading to reduced transmission losses, improved grid stability, and better peak demand management. The paper also emphasizes the current need for energy storage solutions to manage the variability of renewable energy, ensuring a reliable power supply. Furthermore, it discusses the economic benefits of deregulated power markets, where competition drives down energy costs and encourages innovation in grid technologies. The importance of this study lies in its comprehensive analysis of the challenges and opportunities associated with renewable energy integration, along with practical recommendations for adopting SG and microgrid technologies to enhance both economic performance and environmental sustainability. Combined, the findings stress the urgent need for policy frameworks and advanced grid management strategies to support the transition to a more resilient and sustainable energy system in today's power market.